Analysis of Teacher Competency Levels in Islamic Educational Institutions in Indonesia - Lestari, Lestari; Anita Indria; Guslianto, Guslianto; Murni, Emilza Tri; Nuraiman, Nuraiman (STIT Ahlussunnah Bukittinggi, 2024)
This study aims to determine the pedagogical, personal, social, and professional competencies of teachers in supporting the learning process of students at the Senior High School level. This study uses a qualitative descriptive approach with a field research type. Data collection techniques are carried out through observation, interviews, and documentation of teachers and the school environment. The results of the study indicate that: (1) Pedagogical competence includes the ability of teachers to design, implement, and evaluate learning effectively, as well as understanding the characteristics of students; (2) Personal competence is reflected in a stable, mature, wise, noble personality, and the ability to be a role model for students; (3) Social competence includes communication skills, the ability to establish harmonious relationships with students and fellow teachers, and the use of information technology in learning interactions; and (4) Professional competence is demonstrated through in-depth mastery of teaching materials, the selection of appropriate learning strategies and media, and teaching experience that supports the improvement of the quality of education. These findings emphasize the importance of the four dimensions of competence as the main foundation in improving the quality of education and the achievement of learning objectives.